Pengukuran dan Evaluasi dalam Pembelajaran Musik: Kajian Teoritis dan Praktis dalam Lembaga Musik Non Formal - Clarisa Jesika Korina Tiurmauli Hutapea; Athira Fatharani Widagdo; Nandang Budiman; Taswadi Taswadi (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2025)
evaluation in music education within non-formal music institutions, and to identify best practices through a literature review. Methods: The method employed is a literature study that examines various recent academic references relevant to evaluation in music education, particularly in non-formal settings. Results and Discussion: The findings reveal that non-formal music institutions continue to face challenges in implementing appropriate evaluation systems due to a lack of adaptation from formal evaluation frameworks. The discussion highlights the importance of contextual and sustainable evaluation approaches, and emphasizes successful evaluation practices applied in non-formal educational contexts. Conclusion: In conclusion, this article provides both theoretical and practical contributions by offering a guide to developing relevant, applicable, and contextual evaluation systems for non-formal music educators, in order to enhance the quality of music learning and support the development of both students and educators more effectively.